Fiber-reinforced composite

By adopting a laminated structure in the fiber-reinforced composite, combining the skin material layer of the reinforcing fiber and a specific functional group resin and the foam core material layer containing a polyphenylene ether resin, the problem of insufficient heat resistance and bending strength of the composite in a high temperature environment is solved, and efficient thermal performance improvement is achieved.

CN119820942APending Publication Date: 2025-04-15ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311322365.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-12
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing fiber reinforced composites have insufficient heat resistance and insufficient bending strength in high temperature environments, which cannot meet the needs of use in high temperature environments such as the surroundings of the engine room.

Method used

The laminated structure of the skin material layer with reinforcing fibers and specific functional group resins and the foam core material layer containing polyphenylene ether resin is adopted. By optimizing the laminated structure and resin components, the peel strength and bending strength of the composite are improved.

Benefits of technology

It achieves excellent heat resistance and high bending strength in high temperature environments, and meets the needs of the use of fiber reinforced composites in high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004491392490000061
    Figure BDA0004491392490000061
  • Figure BDA0004491392490000281
    Figure BDA0004491392490000281
Patent Text Reader

Abstract

The purpose of the present invention is to provide a fiber-reinforced composite having both heat resistance and bending strength in a high-temperature environment. This fiber-reinforced composite is a laminate having at least two layers including a layer including a skin material and a layer including a core material, and is characterized in that the skin material includes reinforcing fibers and a resin having at least one functional group selected from the group consisting of a carbonyl group, an amino group and a hydroxyl group, and the core material includes a foam. The foam contains a polyphenylene ether resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to fiber reinforced composites. Background Art

[0002] Fiber-reinforced synthetic resins that are reinforced with fibers are lightweight and have high mechanical strength, and therefore have been increasingly used in fields requiring lightweight and high mechanical strength, such as the automotive, shipbuilding, aviation, and medical fields.

[0003] As a material satisfying the above requirements, a fiber-reinforced composite material has been proposed in which a foam is used as a core material and a fiber-reinforced resin is laminated and integrated on the surface of the core material (see Patent Documents 1 and 2).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2015-83365

[0007] Patent Document 2: Japanese Patent Application Publication No. 2017-114081 Summary of the invention

[0008] Problems to be solved by the invention

[0009] However, in the automotive field and the like where fiber-reinforced composites are used, there is an increasing demand for fiber-reinforced composites that can withstand use in higher temperature environments such as around engine rooms, and the fiber-reinforced composite disclosed in Patent Document 1 cannot meet such requirements.

[0010] Patent Document 2 discloses a fiber-reinforced composite material having excellent heat resistance of a core foam at 100° C. and having both rigidity and appearance. However, the inventors' research results have shown that the peel strength between the core material and the skin material is weak, and the bending strength of the fiber-reinforced composite material as a whole is insufficient when used.

[0011] The present invention has been studied to solve the above problems, and an object of the present invention is to provide a fiber-reinforced composite having both heat resistance and flexural strength in a high-temperature environment.

[0012] Means for solving problems

[0013] That is, the present invention is as follows. [1]

[0015] A fiber-reinforced composite material is a laminate of at least two layers including a layer including a skin material and a layer including a core material, wherein:

[0016] The surface material comprises reinforcing fibers and a resin, wherein the resin has at least one functional group selected from the group consisting of a carbonyl group, an amino group, and a hydroxyl group.

[0017] The core material includes a foam, and the foam includes a polyphenylene ether-based resin. [2]

[0019] The fiber-reinforced composite material as described in [1], wherein

[0020] At least a portion of the surface of the layer containing the core material is adjacent to other layers,

[0021] When measured according to GB / T 1457-2005, the peel strength between the layer including the core material and the other layers is 30 N·mm / mm or more. [3]

[0023] The fiber-reinforced composite as described in [1] or [2], wherein the reinforcing fibers are glass fibers. [4]

[0025] The fiber-reinforced composite according to any one of [1] to [3], wherein the reinforcing fibers are continuous reinforcing fibers. [5]

[0027] The fiber-reinforced composite according to any one of [1] to [4], wherein the resin contained in the surface material is a thermosetting resin. [6]

[0029] The fiber-reinforced composite as described in [5], wherein the thermosetting resin is an epoxy resin or a polyurethane resin. [7]

[0031] The fiber-reinforced composite as described in [6], wherein the epoxy resin is at least one selected from the group consisting of bisphenol-type epoxy resins, novolac-type epoxy resins, phenol aralkyl-type epoxy resins, biphenyl-type epoxy resins, and epoxy resins having an aromatic group. [8]

[0033] The fiber-reinforced composite as described in [6] or [7], wherein the polyurethane resin is at least one selected from the group consisting of polyurethane, polyurethane (meth)acrylate, and polyurethane aniline. [9]

[0035] The fiber-reinforced composite as described in [6] or [7], wherein the weight average molecular weight of the epoxy resin is 1,000 to 200,000.

[10]

[0037] The fiber-reinforced composite according to any one of [6] to [9], wherein the weight average molecular weight of the polyurethane resin is 1,000 to 200,000.

[11]

[0039] The fiber-reinforced composite according to any one of [1] to

[10] , wherein the foam is a beads foam.

[12]

[0041] The fiber-reinforced composite according to any one of [1] to

[11] , wherein the foam contains 20 to 80% by mass of a polyphenylene ether-based resin relative to 100% by mass of a resin component contained in the foam.

[13]

[0043] The fiber-reinforced composite according to any one of [1] to

[12] , wherein the flexural modulus at 23°C is 500 MPa to 100 GPa.

[14]

[0045] The fiber-reinforced composite according to any one of [1] to

[13] , wherein the dimensional change rate in the height direction before and after hot pressing at 100° C. is 15% or less.

[15]

[0047] The fiber-reinforced composite according to any one of [1] to

[14] is a laminate comprising the layer including the surface material, the layer including the core material, and the layer including the surface material in this order.

[16]

[0049] The fiber-reinforced composite according to any one of [1] to

[15] , wherein the layer including the skin material and the layer including the core material are fused together.

[17]

[0051] The fiber-reinforced composite according to any one of [1] to

[16] is a structural component in a battery pack undercover of an electric vehicle or a battery pack of an electric vehicle.

[0052] Effects of the Invention

[0053] The fiber-reinforced composite material of the present invention has excellent heat resistance in a high-temperature environment and high flexural strength. DETAILED DESCRIPTION

[0054] The specific embodiment of the present invention (hereinafter also referred to as "this embodiment") is described in detail below. The following embodiment is an example for explaining the present invention, and the present invention is not limited to the following embodiment, and various modifications can be made within the scope of the gist thereof.

[0055] [Fiber reinforced composite]

[0056] The fiber-reinforced composite of the present embodiment is a laminate having at least two layers, a layer including a skin material and a layer including a core material, wherein the skin material includes reinforcing fibers and a resin, the resin has at least one functional group selected from the group consisting of a carbonyl group, an amino group, and a hydroxyl group, and the core material includes a foam, and the foam includes a polyphenylene ether resin.

[0057] In this specification, the resin contained in the surface material may be referred to as "surface material resin", and the resin contained in the foam may be referred to as "foam resin".

[0058] The fiber-reinforced composite of the present embodiment preferably includes at least the above-mentioned layer including the surface material (sometimes referred to as the "surface material layer" in this specification) and the above-mentioned layer including the core material (sometimes referred to as the "core material layer" in this specification), and is more preferably a laminated body including a laminated structure in which the above-mentioned surface material layer and the above-mentioned core material layer are stacked adjacent to each other.

[0059] The surface material layer may be a layer consisting of the surface material alone or may further contain other components. The mass ratio of the surface material relative to 100 mass % of the surface material layer is preferably 90 mass % or more, more preferably 95 mass % or more, and even more preferably 99 mass % or more.

[0060] The core material layer may be a layer consisting only of the core material, or may further contain other components. The mass ratio of the core material relative to 100 mass % of the core material layer is preferably 90 mass % or more, more preferably 95 mass % or more, and further preferably 99 mass % or more.

[0061] The surface material layer and the core material layer may or may not be adjacent to each other.

[0062] It is preferred that the skin material layer be disposed on at least a portion of the surface of the core material layer. The portion of the surface of the core material layer where the skin material layer is disposed may be all or a portion of one or both surfaces of the core material layer.

[0063] The fiber-reinforced composite may further include other layers in addition to the surface material layer and the core material layer. Examples of the other layers include an intermediate layer provided between the surface material layer and the core material layer.

[0064] The fiber-reinforced composite body may be, for example, a two-layer body of a surface material layer / a core material layer, a three-layer body of a surface material layer / an intermediate layer / a core material layer, or a surface material layer / a core material layer / a surface material layer, a four-layer body of a surface material layer / an intermediate layer / a core material layer / a surface material layer, a five-layer body of a surface material layer / an intermediate layer / a core material layer / an intermediate layer / a surface material layer, or may include more layers. With regard to the fiber-reinforced composite body, from the aspect of excellent peel strength, a laminate having a laminate structure in which a surface material layer and a core material layer are connected is preferred, and a laminate having a laminate structure in which a surface material layer, a core material layer, and a surface material layer are sequentially connected is more preferred. From the aspect of light weight and excellent peel strength, a surface material layer / a core material layer or a surface material layer / a core material layer / a surface material layer is further preferred, and a laminate having a laminate structure in which a surface material layer, a core material layer, and a surface material layer are sequentially connected is particularly preferred.

[0065] It should be noted that when multiple sheets of the same surface material are stacked and hot-pressed and the boundary of the surface material cannot be determined, it can be regarded as one surface material layer.

[0066] The fiber-reinforced composite is preferably a laminate having a laminate structure in which a skin material layer and a core material layer are connected, and the skin material layer and the core material layer are fused. Here, fusion means that the skin material layer and the core material layer are tightly bonded, which can be confirmed by measuring the peel strength. The fusion can be a state in which the peel strength measured in the later-described examples is 30N·mm / mm or more.

[0067] (core material)

[0068] The core material includes a foam containing a resin. The core material may be composed of the foam alone or may include the foam and other components.

[0069] -Foam-

[0070] The foam contains a resin (ie, a foam resin), and optionally contains a trace amount of gas, an additive, etc. The foam may be a foam consisting only of a foam resin and a gas.

[0071] The foam is preferably a bead foam. The core material is preferably a bead foam. Examples of the bead foam include bead foams produced using pre-expanded particles described below.

[0072] --Foam Resin--

[0073] The foam resin includes a polyphenylene ether-based resin and optionally includes a resin other than the polyphenylene ether-based resin (hereinafter also referred to as “other resin”).

[0074] ---Polyphenylene ether resin---

[0075] The polyphenylene ether resin refers to a polymer containing a repeating unit represented by the following general formula (1), and examples thereof include a homopolymer composed of a repeating unit represented by the following general formula (1) and a copolymer containing a repeating unit represented by the following general formula (1).

[0076] [Chemistry 1]

[0077]

[0078] [In the formula, R1, R2, R3 and R4 are each independently a monovalent group selected from the group consisting of a hydrogen atom; a halogen atom; an alkyl group; an alkoxy group; a phenyl group; a halogenated alkyl group or a halogenated alkoxy group having at least 2 carbon atoms between the halogen atom and the benzene ring in the general formula (1) (which is a group not containing an α-tertiary carbon).]

[0079] The polyphenylene ether resin is not particularly limited, and examples thereof include poly(2,6-dimethyl-1,4-phenylene) ether, poly(2,6-diethyl-1,4-phenylene) ether, poly(2-methyl-6-ethyl-1,4-phenylene) ether, poly(2-methyl-6-propyl-1,4-phenylene) ether, poly(2,6-dipropyl-1,4-phenylene) ether, poly(2-ethyl-6-propyl-1,4-phenylene) ether, poly(2,6-dibutyl-1,4-phenylene) ether, poly(2,6-dilauryl-1,4-phenylene) ether, poly(2,6-diphenyl-1,4-diphenylene) ether, and poly(2,6-dibutyl-1,4-phenylene) ether. ether, poly(2,6-dimethoxy-1,4-phenylene) ether, poly(2,6-diethoxy-1,4-phenylene) ether, poly(2-methoxy-6-ethoxy-1,4-phenylene) ether, poly(2-ethyl-6-stearyloxy-1,4-phenylene) ether, poly(2,6-dichloro-1,4-phenylene) ether, poly(2-methyl-6-phenyl-1,4-phenylene) ether, poly(2,6-dibenzyl-1,4-phenylene) ether, poly(2-ethoxy-1,4-phenylene) ether, poly(2-chloro-1,4-phenylene) ether, poly(2,6-dibromo-1,4-phenylene) ether, etc. Among them, a polymer comprising repeating units in which R1 and R2 in the general formula (1) are alkyl groups having 1 to 4 carbon atoms, and R3 and R4 are hydrogen atoms or alkyl groups having 1 to 4 carbon atoms is particularly preferred.

[0080] The polyphenylene ether-based resin may be used alone or in combination of two or more.

[0081] The weight average molecular weight of the polyphenylene ether resin is preferably 20,000 to 90,000, and more preferably 50,000 to 75,000. If the weight average molecular weight of the polyphenylene ether resin is less than 20,000, the resin will break during foaming, which is not ideal. If the weight average molecular weight of the polyphenylene ether resin is higher than 90,000, the melt viscosity of the resin becomes too high, and the pressure of the die head may reach the processing upper limit in the granulation process, which is not ideal.

[0082] The weight average molecular weight in this specification refers to the value obtained as follows: measured by gel permeation chromatography (GPC), using a calibration curve obtained by measuring commercially available standard polystyrene (made using the peak molecular weight of standard polystyrene) to obtain the peak molecular weight of the chromatogram, and the obtained value is the weight average molecular weight. Specifically, a gel permeation chromatography (GPC) system HLC-8220 manufactured by Tosoh Corporation is used, and a column Tsk-gel Super HZ2000 (two connected in series) manufactured by Tosoh Corporation is used. Tetrahydrofuran is used as the measuring solvent, and the flow rate of the measuring solvent is 1.0 mL / min and the temperature of the column is 40°C for measurement. Regarding the UV wavelength of the detection unit, it is set to 254 nm in the case of standard polystyrene and 283 nm in the case of polyphenylene ether resin.

[0083] The mass ratio of the polyphenylene ether resin is preferably 20 to 90 mass %, more preferably 20 to 80 mass %, further preferably 30 to 80 mass %, and particularly preferably 35 to 70 mass % relative to the total 100 mass % of the resin components contained in the foam. If the mass ratio is 20 mass % or more, excellent heat resistance and flame retardancy can be obtained; if it is 90 mass % or less, excellent processability can be obtained.

[0084] The mass ratio of the polyphenylene ether-based resin to 100 mass % of the total resin components contained in the core layer is preferably 20 to 90 mass %, more preferably 30 to 80 mass %, and even more preferably 35 to 70 mass %.

[0085] ---Resins other than polyphenylene ether resins (other resins)---

[0086] As the above-mentioned other resins, thermoplastic resins and the like can be cited, for example, polyolefin resins such as polyethylene, polypropylene, and EVA (ethylene-vinyl acetate copolymer); polyvinyl alcohol; polyvinyl chloride; polyvinylidene chloride; ABS (acrylonitrile-butadiene-styrene) resin; AS (acrylonitrile-styrene) resin; polystyrene resin; methacrylic resin; polyamide resin; polycarbonate resin; polyimide resin; polyacetal resin; polyester resin; acrylic resin; cellulose resin; thermoplastic elastomers such as styrene, polyvinyl chloride, polyurethane, polyester, polyamide, 1,2-polybutadiene, and fluororubber; polyamide, polyacetal, polyester, and fluorine-based thermoplastic engineering plastics; and the like. In addition, resins modified and cross-linked within the scope that does not impair the purpose of the present invention can be used. Among them, polystyrene resins are preferred from the aspect of compatibility.

[0087] These may be used alone or in combination of two or more.

[0088] Examples of the polystyrene-based resin include homopolymers of styrene or styrene derivatives and copolymers containing styrene and / or styrene derivatives as main components.

[0089] The styrene derivative is not particularly limited, and examples thereof include o-methylstyrene, m-methylstyrene, p-methylstyrene, tert-butylstyrene, α-methylstyrene, β-methylstyrene, diphenylethylene, chlorostyrene, bromostyrene, and the like.

[0090] Examples of the homopolymer of styrene or a styrene derivative include polystyrene, poly-α-methylstyrene, and polychlorostyrene.

[0091] Examples of copolymers containing styrene and / or styrene derivatives as main components include: styrene-α-olefin copolymers; styrene-butadiene copolymers; styrene-acrylonitrile copolymers; styrene-maleic acid copolymers; styrene-maleic anhydride copolymers; styrene-maleimide copolymers; styrene-N-phenylmaleimide copolymers; styrene-N-alkylmaleimide copolymers; styrene-N-alkyl-substituted phenylmaleimide copolymers; styrene-acrylic acid copolymers; styrene-methacrylic acid copolymers; styrene-methyl acrylate copolymers; styrene-methyl methacrylate copolymers; styrene-n-alkyl acrylate copolymers; styrene-n-alkyl methacrylate copolymers; ethylvinylbenzene-divinylbenzene copolymers; terpolymers such as ABS and butadiene-acrylonitrile-α-methylbenzene copolymers; graft copolymers such as styrene-grafted polyethylene, styrene-grafted ethylene-vinyl acetate copolymers, (styrene-acrylic acid) grafted polyethylene, and styrene-grafted polyamide; and the like.

[0092] These may be used alone or in combination of two or more.

[0093] Furthermore, a rubber component such as butadiene may be added to the polystyrene resin as needed.

[0094] The mass ratio of the rubber component is preferably 1.0 to 20 mass %, and may be, for example, 6 mass %, based on 100 mass % of the polystyrene resin.

[0095] From the viewpoint of processability of the foamed resin, the mass ratio of the other resin relative to 100 mass % of the total of the resin components contained in the foam is preferably 20 to 60 mass %, more preferably 30 to 60 mass %.

[0096] The total mass ratio of the resin component to 100 mass % of the foam is preferably 80 mass % or more, and may be 90 mass % or more and less than 100 mass %.

[0097] --gas--

[0098] The gas is incorporated into the foam resin during the foam production process (described later).

[0099] The gas is not particularly limited, and examples thereof include air, carbon dioxide, various gases used as foaming agents, and aliphatic hydrocarbon-based gases.

[0100] Specific examples of the aliphatic hydrocarbon-based gas include butane and pentane.

[0101] The ratio of the gas (preferably aliphatic hydrocarbon gas) to 100% by volume of the foam resin is preferably 500 ppm by volume or less, more preferably 200 ppm by volume or less, based on the volume of the foam resin.

[0102] It should be noted that the ratio of the above gases can be measured by gas chromatography.

[0103] When the ratio of the gas is 500 volume ppm or less, excellent surface smoothness, adhesion, and strength can be obtained, and post-expansion (bulging) can be suppressed.

[0104] --additive--

[0105] Examples of the additives include flame retardants, rubber components, antioxidants, heat stabilizers, lubricants, pigments, dyes, light resistance improvers, antistatic agents, impact resistance modifiers, nucleating agents such as talc, glass beads, inorganic fillers, and antiblocking agents.

[0106] As flame retardants, there can be mentioned organic flame retardants such as halogen compounds such as bromine compounds, non-halogen compounds such as phosphorus compounds and silicone compounds; inorganic flame retardants such as metal hydroxides represented by aluminum hydroxide and magnesium hydroxide, and antimony compounds represented by antimony trioxide and antimony pentoxide; and the like.

[0107] The physical properties of the foam are described below.

[0108] The foaming ratio of the foam is preferably 1.5 cm 3 / g or more, more preferably 2cm 3 / g or more, and preferably 40cm 3 / g or less, more preferably 25cm 3 Within this range, the advantage of weight reduction can be effectively utilized, and excellent heat resistance can be easily maintained.

[0109] The shape of the foam is not particularly limited and may be appropriately determined depending on the purpose and application. Examples of the foam include molded products, pellets, sheets, threads (filaments), and blocks.

[0110] (Surface material)

[0111] The surface material in the fiber-reinforced composite of the present embodiment contains reinforcing fibers and a resin, and optionally contains additives, etc. The surface material may be a surface material composed only of reinforcing fibers and a resin.

[0112] From the aspect of improving the adhesion between the surface material layer and other layers adjacent to the surface material layer (for example, the core material layer adjacent to the surface material layer), the resin contained in the surface material preferably has at least one functional group selected from the group consisting of a carbonyl group, an amino group and a hydroxyl group. More preferably, the above functional group is present on the surface of the surface material layer adjacent to the core material layer. In addition, it is preferred that the resin having the above functional group is present on the surface of the surface material layer adjacent to the core material layer.

[0113] The resin contained in the surface material layer has at least one functional group selected from the group consisting of a carbonyl group, an amino group, and a hydroxyl group. The analysis can be performed as follows: the cut surface material is used as a sample to extract the resin, and the polypropylene using the obtained resin is subjected to NMR spectrum evaluation to measure the isotactic pentad fraction.

[0114] The mass of the resin having at least one functional group selected from the group consisting of a carbonyl group, an amino group, and a hydroxyl group is set to 100%, and the mass of the functional group in the resin is preferably 1% to 20%, and more preferably 1% to 15%. If the amount of the functional group is within the above range, the peel strength between the core material layer and the surface material layer or the peel strength between the core material layer and the intermediate layer is improved.

[0115] The mass of the functional groups can be calculated by combining solid-state NMR spectroscopy with Fourier transform infrared spectroscopy (FTIR).

[0116] The solid NMR spectrum was measured under the following conditions: As a measurement sample, a surface material was removed from a fiber-reinforced composite, and a resin from which fibers included in the surface material were removed was used.

[0117] · Apparatus: 13C-NMR apparatus ("JNM-CMXP400" manufactured by JEOL Ltd.)

[0118] Observed nucleus: C13

[0119] ·Base material: Adamantane

[0120] Probe: 4mmΦCP probe

[0121] Number of points: 1000 times

[0122] Frequency: 100MHz

[0123] The device used in Fourier transform infrared spectroscopy (FTIR) was JASCO Corporation (FT / IR-6100), and the absorption spectrum was obtained by placing the epidermis layer and the prism in close contact using the total reflection measurement method (ATR). The measurement sample was prepared using the same process as the solid NMR spectroscopy measurement.

[0124] -Reinforcement Fiber-

[0125] The reinforcing fibers may be continuous reinforcing fibers or discontinuous reinforcing fibers, preferably continuous reinforcing fibers. When the reinforcing fibers are continuous reinforcing fibers, the fiber form and arrangement are not limited, and examples thereof include fiber structures such as unidirectionally paralleled long fibers, monofilament bundles, woven fabrics, knitted fabrics, and braids.

[0126] As the type of reinforcing fiber, from the aspect of high strength and high elastic modulus, carbon fiber, glass fiber, aramid fiber, silicon carbide fiber, boron fiber, PBO fiber, high-strength polyethylene fiber, alumina fiber and silicon carbide fiber etc. can be cited. From the aspect of mechanical properties, thermal properties and versatility, glass fiber, carbon fiber and aramid fiber are preferred, and from the aspect of productivity, carbon fiber and glass fiber are preferred. From the aspect of high flame retardancy and improved adhesion with the core material, glass fiber is more preferred.

[0127] These fibers may be used alone or in combination of two or more.

[0128] From the viewpoint of ensuring high rigidity, the tensile modulus of the reinforcing fiber measured in accordance with JIS-K7127 is preferably 200 to 850 GPa.

[0129] The mass ratio of the reinforcing fibers to 100 mass % of the surface material is preferably 40 to 80 mass %.

[0130] From the perspective of improving rigidity and achieving weight reduction, the basis weight of the reinforcing fibers is preferably 50 to 4000 g / m 2 , more preferably 100 to 1000 g / m 2 When there is an interface between the core material layer and the surface material layer, it is preferred that the basis weight of the reinforcing fibers contained in the surface material at the interface satisfies the above range.

[0131] --Fiberglass--

[0132] Glass fiber is a fibrous material made by melting and pulling glass.

[0133] The single fiber fineness of the glass fiber is preferably 0.2 to 3.5 dtex, more preferably 0.4 to 3.0 dtex. If the single fiber fineness is less than 0.2 tex, the resin composition may not be fully impregnated into the glass fiber, resulting in reduced fatigue resistance. In addition, if the single fiber fineness is higher than 3.5 dtex, the fiber surface area per unit volume of the composite reinforcement material is reduced, resulting in reduced mechanical properties.

[0134] In the glass fiber, the number of filaments in one fiber bundle is preferably in the range of 1,000 to 100,000, more preferably 3,000 to 50,000. If the number of filaments is less than 1,000, the fiber arrangement is likely to form an S shape, which is likely to cause strength reduction. In addition, if the number of filaments is greater than 100,000, it is sometimes difficult to impregnate the resin composition during the production or molding of the composite reinforcement material.

[0135] --Sizing agent--

[0136] When glass fibers are selected as reinforcing fibers, a sizing agent (sizing agent) may be used.

[0137] The sizing agent preferably includes at least one selected from the group consisting of a silane coupling agent, an epoxy resin compound, a polyurethane resin compound, and a polyamide resin compound.

[0138] In addition, the above-mentioned sizing agent preferably includes at least one sizing agent with a carbonyl group. The reason is that by utilizing the coating of the sizing agent to make the carbonyl group of the sizing agent located on the surface of the reinforcing fiber, the bonding with the glass fiber can be enhanced. In addition, by making the carbonyl group of the sizing agent present on the surface of the reinforcing fiber, when the reinforcing fiber and the surface material resin are compounded, interaction is exerted at the interface of the two, thereby having high bonding strength, and the strength of the surface material tends to increase. Specifically, it is preferred to include a silane coupling agent with a hydroxyl group, a curing agent containing an isocyanate group, etc.

[0139] The sizing agent preferably contains one or more selected from the group consisting of a silane coupling agent, a lubricant, and a bundling agent, and preferably contains at least a bundling agent or a silane coupling agent.

[0140] In addition, the sizing agent may be composed of a silane coupling agent and a bundling agent, or may be composed of a silane coupling agent, a lubricant, and a bundling agent.

[0141] By using a sizing agent that forms a strong bond between the glass fiber and the resin forming a coating around the glass fiber, a surface material with a small porosity can be obtained.

[0142] The sizing agent may be added to the material to be used or may be contained in the material to be used. For example, a lubricant may be contained in a commercially available thermoplastic resin to be used.

[0143] -Surface material resin-

[0144] Examples of the surface material resin include thermosetting resins and thermoplastic resins, epoxy resins, polyurethane resins, phenol resins, cyanate resins, benzoxazine resins, polyimide resins, unsaturated polyester resins, vinyl ester resins, ABS resins, polyethylene terephthalate resins, nylon resins, maleimide resins, and the like.

[0145] Among them, thermosetting resins that are cured by the addition of external energy such as heat, light, or electron beams are preferred, and specifically, epoxy resins or polyurethane resins are preferred.

[0146] These resins may be used alone or in combination of two or more.

[0147] --Epoxy Resin--

[0148] As epoxy resins, bisphenol-type epoxy resins such as bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, and bisphenol AD ​​epoxy resin can be cited; novolac epoxy resins such as cresol-novolac epoxy resins; phenol aralkyl epoxy resins having a phenylene skeleton and a biphenylene skeleton; biphenyl epoxy resins having a biphenyl skeleton; epoxy resins having an aromatic group; etc., preferably epoxy resins having highly polar functional groups containing carbonyl, amino, and hydroxyl groups. By having the above functional groups, the adhesion to the core material containing the polyphenylene ether resin is improved.

[0149] The above epoxy resins may be used alone or in combination of two or more.

[0150] From the viewpoint of improving the impregnation property into the reinforcing fibers, the weight average molecular weight of the epoxy resin is preferably 1,000 to 200,000, particularly preferably 5,000 to 150,000.

[0151] --Polyurethane resin--

[0152] Examples of the polyurethane resin include polyurethane, polyurethane (meth)acrylate, polyurethane aniline, etc., and there is no limitation as long as it has highly polar functional groups such as carbonyl, amino and hydroxyl. By having such functional groups, the adhesion with the core material containing polyphenylene ether resin is improved.

[0153] The above-mentioned polyurethane resins may be used alone or in combination of two or more.

[0154] From the viewpoint of improving the impregnation property into the reinforcing fibers, the weight average molecular weight of the polyurethane resin is preferably 1,000 to 200,000, particularly preferably 5,000 to 150,000.

[0155] The glass transition temperature of the surface material resin is preferably 80 to 250° C., more preferably 80 to 180° C., from the viewpoint of adhesion to the core material, deformation, and warpage.

[0156] In addition, the glass transition temperature can be measured by the midpoint method according to ASTM-D-3418.

[0157] When the surface material resin is a thermosetting resin, the curing temperature is preferably 80 to 250° C., more preferably 80 to 150° C., from the viewpoints of adhesion to the core material, deformation, and warpage.

[0158] The mass ratio of the surface material resin is preferably 20 to 60 mass %, more preferably 30 to 50 mass %, based on 100 mass % of the surface material, from the viewpoint of adhesion to the core material, deformation, and warping.

[0159] (Middle layer)

[0160] Examples of the intermediate layer include adhesives, bonding agents, double-sided tapes, etc. By including the intermediate layer between the surface material layer and the core material layer, the adhesion between the surface material layer and the core material layer can be improved.

[0161] The intermediate layer preferably contains a resin.

[0162] Examples of the above-mentioned resin include urethane resin, epoxy resin, acrylic resin, phenolic resin, alkyd resin, silicone resin, polyacetal resin, polyester resin, polyamide resin, polyimide resin, nitrocellulose, etc. From the perspective of excellent adhesion between the skin layer and the core layer, it is preferably at least one selected from the group consisting of urethane resins, epoxy resins, acrylic resins, and polyimides having high polarity.

[0163] The mass ratio of the resin is preferably 5 to 90 mass %, more preferably 10 to 90 mass %, and even more preferably 10 to 80 mass %, based on 100 mass % of the intermediate layer.

[0164] [Method for producing fiber-reinforced composite]

[0165] Next, a method for producing the fiber-reinforced composite material according to the present embodiment will be described.

[0166] As a method for producing the fiber-reinforced composite material of the present embodiment, there is mentioned a method of simultaneously molding the core material and the surface material by heating and pressurizing them.

[0167] A method for manufacturing a fiber-reinforced composite according to an example of the present embodiment is as follows: a resin component containing 40 to 80% by mass of a polyphenylene ether resin and a foaming agent are added to a pre-foaming machine for pre-foaming, thereby obtaining pre-foamed particles; next, the obtained pre-foamed particles are added to a molding machine for molding, thereby obtaining a foamed body; next, the obtained foamed body and a surface material containing reinforcing fibers and a resin are added to a molding machine for molding, thereby obtaining a fiber-reinforced composite.

[0168] In addition, pre-expanded particles refer to expandable particles that have not undergone final stage expansion.

[0169] As the core material, a foamed product, a foam sheet, etc. can be used. From the viewpoints of shape imparting property, molding efficiency, etc., it is preferred to mold the beads by foaming.

[0170] More specifically, the method for producing the fiber-reinforced composite preferably includes one or more of the following steps, and more preferably includes all of the following steps:

[0171] a mixture preparation step of preparing a mixture including a resin component containing 40 to 80% by mass of a polyphenylene ether-based resin;

[0172] A blowing agent adding step, adding a blowing agent to the above mixture to prepare a mixture containing a blowing agent;

[0173] A pre-foaming step, wherein the mixture containing the foaming agent is placed in a pre-foaming machine equipped with a steam introduction line, and the mixture containing the foaming agent is pre-foamed while supplying steam to obtain pre-foamed particles;

[0174] A foam preparation step, wherein the pre-foamed particles are placed in a molding machine, and the pre-foamed particles are foamed and molded while supplying steam to obtain a foam;

[0175] A surface material preparation step of impregnating the reinforcing fibers with resin to obtain a surface material; and

[0176] In the molding step, the foam and the surface material are filled into a molding machine, and the foam and the surface material are molded to obtain a fiber-reinforced composite.

[0177] The details of each process are described below.

[0178] (Mixture preparation process)

[0179] In the mixture preparation step, the resin component of the mixture may optionally contain other resins (described above) in addition to the polyphenylene ether resin (preferably 20 to 80% by mass of polyphenylene ether). In addition, the mixture may contain additives (described above) in addition to the resin component.

[0180] The contents of the polyphenylene ether-based resin, other resins, and additives in the resin component (100% by mass) may be as described above.

[0181] (Foaming agent adding process)

[0182] In the blowing agent adding step, it is preferred that a gas blowing agent is injected or a solid blowing agent is mixed and the blowing agent is added (impregnated) into the mixture, thereby obtaining a mixture containing the blowing agent.

[0183] The foaming agent is not particularly limited, and examples thereof include air and gasifiable compounds.

[0184] Examples of compounds that can become gas include inorganic compounds such as carbon dioxide, nitrogen, oxygen, ammonia, hydrogen, argon, helium, and neon; fluorocarbons such as trichlorofluoromethane (R11), dichlorodifluoromethane (R12), chlorodifluoromethane (R22), tetrachlorodifluoroethane (R112), dichlorofluoroethane (R141b), chlorodifluoroethane (R142b), difluoroethane (R152a), HFC-245fa, HFC-236ea, HFC-245ca, and HFC-225ca; saturated hydrocarbons such as propane, n-butane, isobutane, n-pentane, isopentane, and neopentane; Ethers such as ether, diethyl ether, methyl ethyl ether, isopropyl ether, n-butyl ether, diisopropyl ether, furan, furfural, 2-methylfuran, tetrahydrofuran, tetrahydropyran, etc.; ketones such as dimethyl ketone, methyl ethyl ketone, diethyl ketone, methyl n-propyl ketone, methyl n-butyl ketone, methyl isobutyl ketone, methyl n-amyl ketone, methyl n-hexyl ketone, ethyl n-propyl ketone, ethyl n-butyl ketone, etc.; alcohols such as methanol, ethanol, propanol, isopropanol, butanol, isobutanol, tert-butanol, etc.; carboxylates such as methyl formate, ethyl formate, propyl formate, butyl formate, amyl formate, methyl propionate, ethyl propionate, etc.; chlorinated hydrocarbons such as methyl chloride and ethyl chloride, etc. These air or gaseous compounds may be used alone or in combination of two or more.

[0185] Among them, as a foaming agent, inorganic compounds are preferred from the aspect of safety. Gases of inorganic compounds are difficult to dissolve in resins compared with gases of organic compounds such as hydrocarbons, and are easily discharged from the resin after the molding process described later, thereby enabling the molded body to have a more excellent dimensional stability over time. In addition, when using the gas of an inorganic compound, it is not easy to cause plasticization of the resin due to residual gas, and the molded body can show excellent heat resistance at an earlier stage after the molding process described later.

[0186] Among inorganic compounds, carbon dioxide is more preferred from the viewpoints of solubility in resins and ease of handling.

[0187] In the blowing agent adding step, the method of adding (impregnating) the blowing agent into the mixture is not particularly limited, and a generally performed method can be applied.

[0188] Examples of methods for adding (impregnating) a blowing agent include: a method using a suspension system such as water in an aqueous medium (suspension infiltration method); a method using a thermally decomposable blowing agent such as sodium bicarbonate (foaming agent decomposition method); a method in which the blowing agent is brought into contact with the mixture in a liquid phase in an atmosphere above the critical pressure (liquid phase infiltration method); a method in which a blowing agent in a gas phase is brought into contact with the mixture in a high-pressure atmosphere below the critical pressure (gas phase infiltration method); and the like.

[0189] Among the above methods, vapor phase infiltration is particularly preferred.

[0190] Compared with suspension impregnation performed under high temperature conditions, in gas phase impregnation, the solubility of gas in the resin is higher, and it is easy to increase the content of the blowing agent. Therefore, it is easy to achieve a high expansion ratio by gas phase impregnation, and the bubble size in the resin is also easy to become uniform.

[0191] In addition, the foaming agent decomposition method is also carried out under high temperature conditions like the suspension infiltration, which is inconvenient. In addition, in this method, not all of the added thermal decomposition type foaming agent forms gas, so the amount of gas generated tends to be relatively small. Therefore, gas phase infiltration has the advantage of being easy to increase the foaming agent content.

[0192] Furthermore, in the case of gas phase impregnation, compared with the case of liquid phase impregnation, equipment such as a pressure-resistant device and a cooling device can be more easily miniaturized, and equipment costs can be easily reduced.

[0193] The conditions of the gas phase infiltration method are not particularly limited. For example, from the viewpoint of more efficiently dissolving the gas in the resin, the atmospheric pressure is preferably 0.5 to 6.0 MPa, and the atmospheric temperature is preferably 5 to 30°C.

[0194] The ratio of the impregnated gas to the resin is preferably 2 to 10% by mass.

[0195] (Pre-foaming process)

[0196] In the pre-foaming step, there is no particular limitation on the method for causing the mixture containing the foaming agent after containing (impregnating) the foaming agent to foam. For example, the following methods can be used: a method in which the mixture containing the foaming agent is suddenly transferred from a high-pressure atmosphere to a low-pressure atmosphere, thereby causing the gas as the foaming agent dissolved in the mixture containing the foaming agent to expand and foam; a method in which the gas in the mixture containing the foaming agent is expanded and foamed by heating using pressurized steam or the like; and the like. In particular, the latter method of heating and foaming is preferably used because of the advantages of making the bubble size (cell size) inside the molded body as the product uniform and the advantage of controlling the foaming ratio to facilitate the preparation of a molded body with a low foaming ratio.

[0197] Here, when the pre-expanded particles are expanded to a desired expansion ratio, one-stage expansion may be performed, or multi-stage expansion including secondary expansion, tertiary expansion, etc. It should be noted that in the case of multi-stage expansion, it is easy to prepare pre-expanded particles with a high expansion ratio, and from the perspective of reducing the amount of resin used per unit volume, the pre-expanded particles used in molding are preferably pre-expanded particles that have been subjected to multi-stage expansion.

[0198] Particularly in the case of multi-stage foaming, it is preferred to subject the pre-foamed particles to a gas-based pressure treatment before each stage of foaming. The gas used in the pressure treatment is not particularly limited as long as it is inert to the resin, and inorganic gases and hydrofluoroolefins with high safety and low global warming potential are preferred. Examples of inorganic gases include air, carbon dioxide, nitrogen, oxygen, ammonia, hydrogen, argon, helium, and neon. Examples of hydrofluoroolefins include HFO-1234y and HFO-1234ze (E). In particular, air and carbon dioxide are preferred from the perspective of ease of handling and economy. The method for the pressure treatment is not particularly limited, and examples include a method in which the pre-foamed particles are filled into a pressurized tank and gas is supplied into the tank.

[0199] In the pre-foaming step, when the mixture containing the blowing agent is pre-foamed, the pressure of the steam supplied to the pre-foaming machine is preferably 6.0 to 15.0 kg / cm 2 G, more preferably 6.1 to 12.0 kg / cm 2 G. If the introduction pressure is low, the ability to heat the pre-foaming machine is reduced, so the time required to heat up to the specified temperature during pre-foaming becomes longer. As a result, the surface of the pre-foamed particles is easily melted and integrated with adjacent pre-foamed particles, which is called "sticking". The introduction steam pressure is 6.0 kg / cm 2 When the steam pressure is G or more, the steam pressure in the pre-expanding machine rises rapidly, and good pre-expanded particles without blocking are easily obtained.

[0200] The shape of the pre-expanded particles obtained in the pre-expanding step is not particularly limited, and examples thereof include cylindrical, rectangular, spherical, and amorphous pulverized products.

[0201] The size (particle diameter) of the pre-expanded particles is preferably 0.2 to 3 mm. When the size is within this range, the pre-expanded particles have an appropriate size and are easy to handle, and filling during molding is easy to become denser.

[0202] It should be noted that the size of the pre-expanded particles can be measured using a vernier caliper.

[0203] The expansion ratio of the pre-expanded particles obtained in the pre-expanding step is not particularly limited, but is preferably 1.5 to 30 cm 3 / g, more preferably 2 to 20 cm 3 / g. If it is within this range, a foam having excellent heat resistance can be obtained while taking advantage of light weight. When the desired expansion ratio is adjusted in multiple stages, the primary expansion ratio is preferably 1.4 to 10 cm 3Within this range, the cell size in the foam is likely to become uniform, and secondary foaming ability is likely to be imparted.

[0204] The expansion ratio of the pre-expanded particles refers to the ratio of the volume Vp of the pre-expanded particles to the weight Wp of the pre-expanded particles (Vp / Wp). In the present specification, the volume of the pre-expanded particles refers to a volume that cannot be measured with water.

[0205] (Foam Preparation Step)

[0206] In the foam production step, the mold used for molding can be selected according to the final desired shape of the fiber-reinforced composite.

[0207] The conditions for expanding and molding the pre-expanded particles are not particularly limited.

[0208] The foam preparation process is not particularly limited, and for example, pre-foamed particles are filled into a molding die and heated, thereby causing the pre-foamed particles to fuse with each other while foaming, and then the resultant is solidified by cooling and molding. Here, the filling method of the pre-foamed particles is not particularly limited, and for example, the following methods can be cited: a cracking method in which pre-foamed particles are filled in a state in which the mold is slightly opened; a compression method in which pressurized pre-foamed particles are filled in a state in which the mold is kept closed; a compression cracking method in which pressurized pre-foamed particles are filled in a mold and then the cracking method is performed; and the like.

[0209] In the foam preparation process, before the pre-foamed particles are filled into the molding die, the pre-foamed particles are preferably subjected to a gas-based pressure treatment. By applying the pressure treatment at this stage, a certain gas pressure can be given to the bubbles in the pre-foamed particles, so that the bubble size (cell size) inside the particles is uniform. The gas used in the pressure treatment is not particularly limited, and from the aspect of dimensional stability, inorganic gases are preferably used. The method for the inorganic gas and the pressure treatment is the same as the case of the gas-based pressure treatment implemented on the pre-foamed particles before foaming in the above-mentioned pre-foaming process.

[0210] The expansion ratio of the foam obtained in the foam preparation step is not particularly limited, but is preferably 1.5 to 40 cm 3 / g, more preferably 2 to 25 cm 3 Within this range, a foam having excellent heat resistance can be obtained while taking advantage of weight reduction.

[0211] The expansion ratio of the foam refers to the ratio of the volume Vb of the foam to the weight Wb of the foam (Vb / Wb). In the present specification, the volume of the foam refers to a volume that cannot be measured with water.

[0212] (Surface material preparation process)

[0213] In the skin material preparation process, the reinforcing fibers are immersed in a molten resin, or the molten resin is sprayed onto the reinforcing fibers so that the resin is impregnated into the reinforcing fibers to obtain the skin material. The skin material can also be prepared in the form of a fabric prepreg.

[0214] Note that after the reinforcing fibers are impregnated with the resin, the resin may be cured by light or heat.

[0215] In particular, in sheet-like surface materials, the basis weight of the fibers is preferably 50 to 4000 g / m 2 , more preferably 100 to 1000 g / m 2 , for example, it can be 200g / m 2 .

[0216] When the shape of the fiber-reinforced composite is also a sheet shape, it may be as described in the fiber-reinforced composite of the present embodiment.

[0217] (Molding process)

[0218] In the molding step, the foam and the surface material can be filled in a molding machine in a desired arrangement state and molded simultaneously.

[0219] It should be noted that the foamed body may be further foamed in the molding step.

[0220] In this molding process, for example, in the case of manufacturing a sheet-like composite body covered with surface materials on both sides, the sheet-like foam body can be filled into the molding machine in a manner that the sheet-like foam body is located between two sheets of surface materials. In the case of manufacturing a block-like composite body covered with surface materials, the block-like foam body can be filled into the molding machine in a manner that the block-like foam body is wrapped by the sheet-like surface materials. In the case of manufacturing a linear composite body covered with surface materials, the linear foam body can be filled into the molding machine in a manner that the linear surface materials are wrapped.

[0221] In the molding process, first, the temperature is maintained at 80 to 150° C., preferably 100 to 120° C., for 0 to 5 minutes, preferably 1 to 3 minutes, without applying pressure, and then maintained at 80 to 150° C., preferably 100 to 120° C., for 5 to 30 minutes, preferably 10 to 20 minutes, under a pressure of 0 to 3 MPa, preferably 0.1 to 1 MPa.

[0222] Thus, by maintaining the surface material under high temperature conditions without applying pressure before pressing, the surface material can be heated uniformly to obtain surface smoothness.

[0223] The fiber-reinforced composite material of the present embodiment can be suitably used for, for example, a battery pack bottom cover of an electric vehicle or a structural member in a battery pack of an electric vehicle.

[0224] The physical properties of the fiber-reinforced composite material according to the present embodiment are described below.

[0225] In the fiber reinforced composite of the present embodiment, when at least a portion of the surface of the core material layer is adjacent to other layers, the peel strength between the core material layer and the other layers is preferably 50 N·mm / mm or more, more preferably 50 N·mm / mm or more and 500 N·mm / mm or less, and further preferably 50 N·mm / mm or more and 300 N·mm / mm or less. By making the peel strength within the above range, the adhesion between the core material and other layers can be improved, and the bending strength of the fiber reinforced composite as a whole can be improved.

[0226] For example, when the fiber reinforced composite of the present embodiment is a laminate and the surface material layer and the core material layer are adjacent, the peel strength between the surface material layer and the core material layer preferably satisfies the above range from the perspective of improving the adhesion between the surface material layer and the core material layer.

[0227] When the fiber reinforced composite of the present embodiment includes a plurality of core material layers, the peel strength between at least one core material layer and the other adjacent layers is preferably within the above range, and the peel strength between all core material layers and the other adjacent layers is more preferably within the above range.

[0228] When at least a part of both surfaces of the core layer is adjacent to other layers, the peel strength between one surface and the adjacent other layer is preferably within the above range, and more preferably between both surfaces and the adjacent other layers.

[0229] The peel strength can be measured by the method described in Examples below.

[0230] The compressive elastic modulus of the core material layer of the present embodiment at 80° C. is 15 MPa to 250 MPa, more preferably 30 MPa to 200 MPa. By setting the compressive elastic modulus to be within the above range, the fiber-reinforced composite can be produced with a designed thickness.

[0231] The compressive elastic modulus can be measured using a compression SS curve of a universal measuring machine. The measurement method is based on GB / T8813-2020.

[0232] The flexural modulus of the fiber-reinforced composite material of the present embodiment at 23° C. is preferably 100 MPa to 100 GPa, more preferably 200 MPa to 50 GPa, and even more preferably 200 MPa to 30 GPa. Alternatively, it may be 500 MPa to 100 GPa.

[0233] The flexural modulus can be measured by the method described in Examples below.

[0234] The fiber reinforced composite of this embodiment preferably has a dimensional change rate in the height direction before and after hot pressing at 120° C. of 15% or less, more preferably 10% or less. When the dimensional change rate is within the above range, the fiber reinforced composite has high dimensional accuracy.

[0235] The fiber-reinforced composite of the present embodiment preferably has a dimensional change rate in the height direction before and after hot pressing at 100° C. of 15% or less, more preferably 10% or less.

[0236] The dimensional change rate in the height direction can be measured by the method described in Examples below.

[0237] The apparent density of the fiber-reinforced composite of the present embodiment is preferably 0.05 to 1.5 g / cm 3 By setting the above apparent density to be within the above range, both weight reduction and mechanical strength can be achieved.

[0238] It should be noted that the apparent density of a fiber-reinforced composite refers to the weight W (g) of the fiber-reinforced composite relative to the volume V (cm 3 ) ratio (W / V).

[0239] The size of the fiber-reinforced composite of the present embodiment can be appropriately determined according to the purpose and application. The thickness of the surface material layer can be approximately 0.1 to 3 mm.

[0240] In addition, when the fiber-reinforced composite is a laminate including a surface material layer, the thickness of the surface material may be the thickness of one surface material layer.

[0241] Example

[0242] The present invention will be described below based on Examples and Comparative Examples, but the present invention is not limited thereto.

[0243] The evaluation method is as follows.

[0244] (1) Peel strength

[0245] According to GB / T 1457-2005, the peel strength between the skin material layer and the core material layer in the composites obtained in the examples and comparative examples was determined. Specifically, the composite was allowed to stand for 24 hours in a room controlled at a standard temperature of 23°C and a relative humidity of 50% to adjust the state, and the composite after the adjustment was subjected to measurement using Exceed E45.105 to measure the peel strength between the skin material layer and the foam layer. The results are shown in Table 1.

[0246] (2) Flexural modulus: standard temperature 23°C

[0247] The flexural modulus (GPa) of the fiber-reinforced composites obtained in the examples and comparative examples was determined in accordance with JIS-K7221. Specifically, the composite was allowed to stand for 24 hours in a room controlled at a standard temperature of 23°C and a relative humidity of 50% to adjust the state, and the composite after the adjustment was subjected to measurement using AUTOGRAPH AG-5000D (manufactured by Shimadzu Corporation), and the flexural modulus was calculated according to the calculation formula specified in JIS. The results are shown in Table 1.

[0248] (4) Bending strength: standard temperature 100°C

[0249] The flexural strength (MPa) of the fiber-reinforced composites obtained in the examples and comparative examples was determined in accordance with JIS-K7221. Specifically, the composite was subjected to measurement using AUTOGRAPH AG-5000D (manufactured by Shimadzu Corporation) in an oven controlled at a standard temperature of 100°C, and the flexural strength was calculated according to the calculation formula specified in JIS. The results are shown in Table 1.

[0250] (3) Dimensional change rate of thickness in the height direction

[0251] The thickness (mm) of the fiber-reinforced composite obtained in the examples and comparative examples was measured using a vernier caliper. Afterwards, the fiber-reinforced composite was hot-pressed for 30 minutes in the thickness direction at a temperature of 100°C and a pressure of 800 MPa. The thickness (mm) of the fiber-reinforced composite after hot pressing was then measured. The dimensional change rate was then determined according to the following formula. The results are shown in Table 1.

[0252] Dimensional change rate (%) = {(thickness before hot pressing (mm) - thickness after hot pressing (mm)) / thickness before hot pressing (mm)} × 100

[0253] (4) Apparent density

[0254] After measuring the weight W (g) of the fiber-reinforced composites obtained in the examples and comparative examples, the three sides of the sheet-like fiber-reinforced composites were measured with a vernier caliper to calculate their volumes V (cm 3 ). And the ratio of weight W to volume V (W / V) (g / cm 3 The results are shown in Table 1.

[0255] (5) Surface smoothness - appearance

[0256] The surfaces of the fiber-reinforced composites obtained in Examples and Comparative Examples and the bonding state between the surface material layer and the core material layer were visually observed and evaluated as follows.

[0257] ◎ (Excellent): The surface smoothness and adhesion between the surface material and the core material are both good.

[0258] ○ (good): There is no problem in practical surface smoothness, but some bulging (warping) is observed between the surface material and the core material.

[0259] × (unacceptable): The core material shrinks and the thickness of the composite is equivalent to the thickness of the skin material alone.

[0260] [Example 1]

[0261] A fiber having a basis weight of 200 g / m2 was prepared, which was composed of glass fiber (manufactured by Owens Corning, ME1510, etc.) with a tensile elastic modulus of 250 GPa and an epoxy resin (containing a carbonyl group in the polymer unit, a carbonyl group content of 12% by mass in the polymer, and a weight average molecular weight of 8000) with a curing temperature of 120°C. 2 , prepare 2 sheets of fabric prepreg with a glass fiber content of 60% by mass as surface materials.

[0262] In addition, 60% by mass of a polyphenylene ether resin (PPE) (S201A manufactured by Asahi Kasei Chemicals Corporation), 18% by mass of a non-halogen flame retardant (bisphenol A-bis(diphenyl phosphate) (BBP)), 10% by mass of an impact-resistant polystyrene resin (HIPS) having a rubber concentration of 6% by mass (the rubber component content in the base resin is 0.6% by mass), and 12% by mass of a general-purpose polystyrene resin (PS) (GP685 manufactured by PS Japan Co., Ltd.) were used, and they were heated, melt-kneaded, and extruded to prepare base resin pellets as a core material.

[0263] According to the method described in Example 1 of Japanese Patent Gazette No. 4-372630, substrate resin pellets are placed in a pressure-resistant container, the gas in the container is replaced with dry air, and then carbon dioxide (gas) is injected as a foaming agent. The substrate resin pellets are impregnated with 7% by mass of carbon dioxide under the conditions of pressure 3.2 MPa and temperature 11°C for 3 hours.

[0264] Thereafter, the base resin pellets were foamed with pressurized steam in a pre-foaming machine while rotating a stirring blade at 77 rpm to obtain expanded beads.

[0265] The expanded beads were subjected to a pressure treatment by increasing the pressure to 0.5 MPa over 1 hour and then maintaining the pressure at 0.5 MPa for 8 hours.

[0266] The foamed beads are filled into an in-mold molding die having steam holes, heated with pressurized steam to expand and fuse the foamed beads to each other, and then cooled and taken out from the molding die to obtain a foamed beads molded body (resin foam).

[0267] The concentration of the aliphatic hydrocarbon gas in the obtained foam was measured and found to be below the detection limit (50 volume ppm).

[0268] The obtained foam was used as a core material, and one sheet of the surface material prepared as described above was stacked on each of the upper and lower surfaces of the core material. Next, the stack was kept at 120°C for 3 minutes without applying pressure, and then kept for 15 minutes while being pressurized at a surface pressure of 0.4 MPa, thereby simultaneously molding the surface material and the core material to obtain a fiber-reinforced composite of surface material layer / core material layer / surface material layer. The results of the evaluation using the obtained fiber-reinforced composite are shown in Table 1.

[0269] It should be noted that the peel strength between the core material layer and the surface material layer is the same value on any surface of the core material layer.

[0270] [Example 2]

[0271] A fiber having a basis weight of 200 g / m2 was prepared, which was composed of glass fiber (manufactured by Owens Corning, ME1510, etc.) with a tensile elastic modulus of 250 GPa and an epoxy resin (containing hydroxyl groups in the polymer unit, 8% by mass of hydroxyl groups in the polymer, and a weight average molecular weight of 5,000) with a curing temperature of 120°C. 2 , 4 sheets of fabric prepreg with a glass fiber content of 60% by mass are prepared as surface materials.

[0272] The same method as in Example 1 was used to produce and evaluate the resin foam, except that two skin materials were placed on each of the upper and lower surfaces of the resin foam. The results are shown in Table 1.

[0273] It should be noted that the peel strength between the core material layer and the surface material layer is the same value on any surface of the core material layer.

[0274] [Example 3]

[0275] A fiber having a basis weight of 200 g / m2 was prepared, which was composed of glass fiber having a tensile elastic modulus of 250 GPa (manufactured by Owens Corning, ME1510, etc.) and a polyurethane resin having a curing temperature of 100°C (containing an amino group in the polymer unit, an amino group content of 10% by mass in the polymer, and a weight average molecular weight of 3,000). 2 , prepare 2 sheets of fabric prepreg with a glass fiber content of 60% by mass as surface materials.

[0276] As the core material, 60% by mass of a polyphenylene ether-based resin (PPE) and 40% by mass of a polystyrene-based resin were heated, melt-kneaded and extruded in an extruder to prepare a mixture.

[0277] The obtained mixture was placed in a pressure-resistant container of a pre-foaming machine, and after replacing the gas in the container with dry air, carbon dioxide (gas) was injected as a foaming agent to impregnate the mixture with carbon dioxide under conditions of a pressure of 3.0 MPa and a temperature of 10° C. for 3 hours.

[0278] Then, the steam pressure was 6 kg / cm 2 G is pre-foamed to obtain pre-foamed particles.

[0279] The pre-expanded particles were placed in a pressurizing and heating device, and air was injected as a pressure source. The pressure was increased to 0.4 MPa over 4 hours at 23° C., and then maintained at 0.4 MPa for 4 hours to perform a pressurizing treatment.

[0280] The pre-foamed particles are filled into a molding die (internal dimensions: 312 mm×312 mm×10 mm) having steam holes, heated with pressurized steam to expand and fuse the pre-foamed particles, and then cooled and taken out from the molding die to obtain a foamed body.

[0281] The results are shown in Table 1, except that the foam obtained with the above composition was used as a core material and the surface material prepared as above was used, production and evaluation were carried out in the same manner as in Example 1.

[0282] It should be noted that the peel strength between the core material layer and the surface material layer is the same value on any surface of the core material layer.

[0283] [Example 4]

[0284] A fiber having a basis weight of 200 g / m2 was prepared, which was composed of glass fiber (manufactured by Owens Corning, ME1510, etc.) with a tensile elastic modulus of 250 GPa and a polyurethane resin (containing hydroxyl groups in the polymer unit, the hydroxyl content in the polymer being 14% by mass, and a weight average molecular weight of 4500) with a curing temperature of 100°C. 2 , 4 sheets of fabric prepreg with a glass fiber content of 60% by mass are prepared as surface materials.

[0285] The skin material prepared as described above was used, and two skin materials were arranged on the upper and lower surfaces of the resin foam, respectively. As for the core material, 40% by mass of polyphenylene ether resin (PPE) and 60% by mass of polystyrene resin were heated and melt-kneaded by an extruder, and then extruded to prepare a mixture. The same production and evaluation were performed as in Example 3. The results are shown in Table 1.

[0286] It should be noted that the peel strength between the core material layer and the surface material layer is the same value on any surface of the core material layer.

[0287] [Example 5]

[0288] A fiber having a basis weight of 200 g / m2 was prepared, which was composed of glass fiber (manufactured by Owens Corning, ME1510, etc.) with a tensile elastic modulus of 250 GPa and a polyurethane resin (containing hydroxyl groups in the polymer unit, the hydroxyl content in the polymer being 14% by mass, and a weight average molecular weight of 4500) with a curing temperature of 100°C. 2 , 4 sheets of fabric prepreg with a glass fiber content of 60% by mass are prepared as surface materials.

[0289] The skin material prepared as described above was used, and two skin materials were arranged on the upper and lower surfaces of the resin foam, respectively. As for the core material, 38% by mass of polyphenylene ether resin (PPE) and 62% by mass of polystyrene resin were heated and melt-kneaded by an extruder, and then extruded to prepare a mixture. The same production and evaluation were performed as in Example 3. The results are shown in Table 1.

[0290] It should be noted that the peel strength between the core material layer and the surface material layer is the same value on any surface of the core material layer.

[0291] [Example 6]

[0292] A fiber having a basis weight of 200 g / m2 was prepared, which was composed of glass fiber (manufactured by Owens Corning, ME1510, etc.) with a tensile elastic modulus of 250 GPa and a polyurethane resin (containing hydroxyl groups in the polymer unit, the hydroxyl content in the polymer being 14% by mass, and a weight average molecular weight of 4500) with a curing temperature of 100°C. 2 , 4 sheets of fabric prepreg with a glass fiber content of 60% by mass are prepared as surface materials.

[0293] The skin material prepared as described above was used, and two skin materials were arranged on the upper and lower surfaces of the resin foam, respectively. As for the core material, 35 mass % of polyphenylene ether resin (PPE) and 65 mass % of polystyrene resin were heated and melt-kneaded by an extruder, and then extruded to prepare a mixture. The same production and evaluation were performed as in Example 3. The results are shown in Table 1.

[0294] It should be noted that the peel strength between the core material layer and the surface material layer is the same value on any surface of the core material layer.

[0295] [Example 7]

[0296] A fiber having a basis weight of 200 g / m2 was prepared, which was composed of glass fiber (manufactured by Owens Corning, ME1510, etc.) with a tensile elastic modulus of 250 GPa and a polyurethane resin (containing hydroxyl groups in the polymer unit, the hydroxyl content in the polymer being 14% by mass, and a weight average molecular weight of 4500) with a curing temperature of 100°C. 2 , 4 sheets of fabric prepreg with a glass fiber content of 60% by mass are prepared as surface materials.

[0297] The skin material prepared as described above was used, and two skin materials were arranged on the upper and lower surfaces of the resin foam, respectively. As for the core material, 20% by mass of polyphenylene ether resin (PPE) and 80% by mass of polystyrene resin were heated and melt-kneaded by an extruder, and then extruded to prepare a mixture. The same production and evaluation were performed as in Example 3. The results are shown in Table 1.

[0298] It should be noted that the peel strength between the core material layer and the surface material layer is the same value on any surface of the core material layer.

[0299] [Example 8]

[0300] A fiber having a basis weight of 200 g / m2 was prepared, which was composed of glass fiber (manufactured by Owens Corning, ME1510, etc.) with a tensile elastic modulus of 250 GPa and a polyurethane resin (containing hydroxyl groups in the polymer unit, the hydroxyl content in the polymer being 14% by mass, and a weight average molecular weight of 4500) with a curing temperature of 100°C. 2 , 4 sheets of fabric prepreg with a glass fiber content of 60% by mass are prepared as surface materials.

[0301] The skin material prepared as described above was used, and two skin materials were arranged on the upper and lower surfaces of the resin foam, respectively. As for the core material, 50% by mass of polyphenylene ether resin (PPE) and 50% by mass of polystyrene resin were heated and melt-kneaded by an extruder, and then extruded to prepare a mixture. The same production and evaluation were performed as in Example 3. The results are shown in Table 1.

[0302] It should be noted that the peel strength between the core material layer and the surface material layer is the same value on any surface of the core material layer.

[0303] [Example 9]

[0304] A fiber having a basis weight of 200 g / m2 was prepared, which was composed of glass fiber (manufactured by Owens Corning, ME1510, etc.) with a tensile elastic modulus of 250 GPa and a polyurethane resin (containing an amino group in the polymer unit, the amino group content in the polymer being 10% by mass, and a weight average molecular weight of 4000) with a curing temperature of 100°C. 2, prepare 2 sheets of fabric prepreg with a glass fiber content of 60% by mass as surface materials.

[0305] As for the core material, 100% by mass of a modified polyphenylene ether resin (polyphenylene ether (PPE) component: 40% by mass, styrene (PS) component: 60% by mass) was pressed in, and butane was pressed in the middle of the extruder at 0.7% by mass relative to the composition to produce a foam sheet of the modified polyphenylene ether resin.

[0306] The results are shown in Table 1, except that the obtained foam was used as a core material and the surface material prepared as described above was used, production and evaluation were carried out in the same manner as in Example 1.

[0307] It should be noted that the peel strength between the core material layer and the surface material layer is the same value on any surface of the core material layer.

[0308] [Example 10]

[0309] A fiber having a basis weight of 200 g / m2 was prepared, which was composed of glass fiber having a tensile elastic modulus of 250 GPa (manufactured by Owens Corning, ME1510, etc.) and an epoxy resin having a curing temperature of 120° C. (containing carbonyl and amino groups in the polymer unit, carbonyl content in the polymer of 8% by mass, amino content in the polymer of 6% by mass, and weight average molecular weight of 5,000). 2 , 4 sheets of fabric prepreg with a glass fiber content of 60% by mass are prepared as surface materials.

[0310] The same method as in Example 1 was used to produce and evaluate the resin foam, except that two skin materials were placed on each of the upper and lower surfaces of the resin foam. The results are shown in Table 1.

[0311] It should be noted that the peel strength between the core material layer and the surface material layer is the same value on any surface of the core material layer.

[0312] [Example 11]

[0313] A fiber having a basis weight of 200 g / m2 was prepared, which was composed of glass fiber having a tensile elastic modulus of 250 GPa (manufactured by Owens Corning, ME1510, etc.) and an epoxy resin having a curing temperature of 120°C (containing a carbonyl group in the polymer unit, a carbonyl group content of 12% by mass in the polymer, and a weight average molecular weight of 4,000). 2 , prepare 2 sheets of fabric prepreg with a glass fiber content of 60% by mass as surface materials.

[0314] The production and evaluation were performed in the same manner as in Example 1, except that two surface materials were arranged only on the upper surface of the resin foam. The results are shown in Table 1.

[0315] [Example 12]

[0316] A fiber having a basis weight of 200 g / m2 was prepared, which was composed of glass fiber having a tensile elastic modulus of 250 GPa (manufactured by Owens Corning, ME1510, etc.) and an epoxy resin having a curing temperature of 120°C (containing a carbonyl group in the polymer unit, a carbonyl group content of 12% by mass in the polymer, and a weight average molecular weight of 5,000). 2 , 4 sheets of fabric prepreg with a glass fiber content of 60% by mass are prepared as surface materials.

[0317] The same method as in Example 1 was used to produce and evaluate the resin foam, except that two skin materials were placed on each of the upper and lower surfaces of the resin foam. The results are shown in Table 1.

[0318] It should be noted that the peel strength between the core material layer and the surface material layer is the same value on any surface of the core material layer.

[0319] [Comparative Example 1]

[0320] A fiber having a basis weight of 200 g / m2 was prepared, which was composed of glass fiber (manufactured by Owens Corning, ME1510, etc.) with a tensile elastic modulus of 250 GPa and an epoxy resin (containing a vinyl group in the polymer unit, the vinyl content in the polymer being 8% by mass, containing no carbonyl group, amino group, or hydroxyl group, and having a weight average molecular weight of 50,000) with a curing temperature of 120°C. 2 , prepare 2 sheets of fabric prepreg with a glass fiber content of 60% by mass as surface materials.

[0321] As for the core material, 60% by mass of polyphenylene ether resin (PPE) (manufactured by Asahi Kasei Chemicals Corporation, S201A), 18% by mass of non-halogen flame retardant, 10% by mass of high-impact polystyrene resin (HIPS) with a rubber concentration of 6% by mass, and 12% by mass of general-purpose polystyrene resin (PS) (manufactured by PS Japan Co., Ltd., GP685) were used. They were heated, melt-kneaded and extruded by an extruder. The obtained mixture was placed in a pressure-resistant container of a pre-foaming machine, and the gas in the container was replaced with dry air. Then, carbon dioxide (gas) as a foaming agent was injected, and the carbon dioxide was impregnated into the mixture under the conditions of a pressure of 3.0 MPa and a temperature of 10°C for 3 hours. The production and evaluation were carried out in the same manner as in Example 1.

[0322] In the composite of Comparative Example 1, the flexural modulus at the standard temperature was obtained, but the skin material layer and the core material layer were peeled off, and a sufficient flexural modulus could not be obtained.

[0323] [Comparative Example 2]

[0324] A fiber having a basis weight of 200 g / m2 was prepared, which was composed of glass fiber having a tensile elastic modulus of 250 GPa (manufactured by Owens Corning, ME1510, etc.) and a polypropylene resin having a curing temperature of 120°C (containing an alkyl group in the polymer unit, the alkyl content in the polymer being 10% by mass, and containing no carbonyl group, amino group, or hydroxyl group at all, and having a weight average molecular weight of 3,000). 2 , prepare 2 sheets of fabric prepreg with a glass fiber content of 60% by mass as surface materials.

[0325] 40% by mass of a core material polyphenylene ether-based resin (PPE) and 60% by mass of a polystyrene-based resin were heated, melt-kneaded and extruded in an extruder to prepare a mixture.

[0326] The obtained mixture was placed in a pressure-resistant container of a pre-foaming machine, and the gas in the container was replaced with dry air. Carbon dioxide (gas) was injected as a foaming agent, and the carbon dioxide was impregnated into the mixture under the conditions of a pressure of 3.0 MPa and a temperature of 10°C for 3 hours. The production and evaluation were carried out in the same manner as in Example 1, except for this.

[0327] In the composite of Comparative Example 2, the flexural modulus at the standard temperature was obtained, but the skin material layer and the core material layer were peeled off, and a sufficient flexural modulus could not be obtained.

[0328] [Comparative Example 3]

[0329] A fiber having a basis weight of 200 g / m2 was prepared, which was composed of glass fiber having a tensile elastic modulus of 250 GPa (manufactured by Owens Corning, ME1510, etc.) and an epoxy resin having a curing temperature of 120°C (containing a carbonyl group in the polymer unit, a carbonyl group content of 8% by mass in the polymer, and a weight average molecular weight of 4,000). 2 , prepare 2 sheets of fabric prepreg with a glass fiber content of 60% by mass as surface materials.

[0330] Production and evaluation were carried out in the same manner as in Example 1 except that Kanepal (registered trademark) 10 times polystyrene resin foam manufactured by Kaneka Corporation was used as the core material and the surface material prepared as described above was used.

[0331] In the composite of Comparative Example 3, the core material melted and a reinforced composite could not be obtained.

[0332]

Claims

1. A fiber-reinforced composite material, which is a laminate of at least two layers including a layer including a skin material and a layer including a core material, wherein: The surface material comprises reinforcing fibers and a resin, wherein the resin has at least one functional group selected from the group consisting of a carbonyl group, an amino group, and a hydroxyl group. The core material includes a foam, and the foam includes a polyphenylene ether-based resin.

2. The fiber-reinforced composite according to claim 1, wherein: At least a portion of the surface of the layer containing the core material is adjacent to other layers, When measured according to GB / T 1457-2005, the peel strength between the layer including the core material and the other layers is 30 N·mm / mm or more.

3. The fiber-reinforced composite according to claim 1 or 2, wherein: The reinforcing fiber is glass fiber.

4. The fiber-reinforced composite according to claim 1 or 2, wherein: The reinforcing fibers are continuous reinforcing fibers.

5. The fiber-reinforced composite according to claim 1 or 2, wherein: The resin contained in the surface material is a thermosetting resin.

6. The fiber-reinforced composite body according to claim 5, wherein: The thermosetting resin is epoxy resin or polyurethane resin.

7. The fiber-reinforced composite body according to claim 6, wherein: The epoxy resin is at least one selected from the group consisting of bisphenol epoxy resins, novolac epoxy resins, phenol aralkyl epoxy resins, biphenyl epoxy resins, and epoxy resins having an aromatic group.

8. The fiber-reinforced composite body according to claim 6, wherein: The polyurethane resin is at least one selected from the group consisting of polyurethane, polyurethane (meth)acrylate, and polyurethane aniline.

9. The fiber-reinforced composite according to claim 6 or 7, wherein: The weight average molecular weight of the epoxy resin is 1,000 to 200,000.

10. The fiber-reinforced composite according to claim 6 or 8, wherein: The polyurethane resin has a weight average molecular weight of 1,000 to 200,000.

11. The fiber-reinforced composite according to claim 1 or 2, wherein: The foamed body is a bead foamed body.

12. The fiber-reinforced composite according to claim 1 or 2, wherein: The foam contains 20 to 80% by mass of a polyphenylene ether-based resin relative to 100% by mass of a resin component contained in the foam.

13. The fiber-reinforced composite according to claim 1 or 2, wherein: The flexural modulus at 23°C is 500 MPa or more and 100 GPa or less.

14. The fiber-reinforced composite according to claim 1 or 2, wherein: The dimensional change rate in the height direction before and after hot pressing at 100° C. is 15% or less. 15 . The fiber-reinforced composite material according to claim 1 , which is a laminate comprising the layer comprising the surface material, the layer comprising the core material, and the layer comprising the surface material in this order.

16. The fiber-reinforced composite according to claim 1 or 15, wherein: The layer including the skin material and the layer including the core material are fused together.

17. The fiber-reinforced composite body according to claim 1 or 2, which is a structural member in a battery pack bottom cover of an electric vehicle or a battery pack of an electric vehicle.

Citation Information

Patent Citations

  • Lowly expanded polyolefin resin particle and its production

    JP1992372630A

  • Sandwich structure, production method thereof and structure formed by processing sandwich structure

    JP2015083365A

  • Fiber-reinforced composite body

    JP2017114081A